2021
DOI: 10.1177/19476035211007909
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Angular Resolution and b Value on Diffusion Tensor Imaging in Knee Joint

Abstract: Objective To investigate the influences of the diffusion gradient directions (angular resolution) and the strength of the diffusion gradient ( b value) on diffusion tensor imaging (DTI) metrics and tractography of various connective tissues in knee joint. Design Two rat knee joints were scanned on a preclinical 9.4-T system using a 3-dimensional diffusion-weighted spin echo pulse sequence. One protocol with b value of 500, 1500, and 2500 s/mm2 were acquired separately using 43 diffusion gradient directions. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…Previous studies have demonstrated that the height of the hypertrophic and proliferative zones increases during periods of increased growth velocity and that linear growth can be expressed as Growth = N * h max 32 (Growth is the 24 h growth in μm; N is the number of chondrocytes created each day in the proliferative zone; h max is the average height of fully mature chondrocytes [μm] in the hypertrophic zone). Similar patterns in the articular and physeal cartilage have been described in experimental DTI studies in rats 19 , 20 as well in human cartilage. 33 The latter study showed that when DTI was performed perpendicular to the transitional zone, type II collagen appeared sideways in the central portion of the articular cartilage.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Previous studies have demonstrated that the height of the hypertrophic and proliferative zones increases during periods of increased growth velocity and that linear growth can be expressed as Growth = N * h max 32 (Growth is the 24 h growth in μm; N is the number of chondrocytes created each day in the proliferative zone; h max is the average height of fully mature chondrocytes [μm] in the hypertrophic zone). Similar patterns in the articular and physeal cartilage have been described in experimental DTI studies in rats 19 , 20 as well in human cartilage. 33 The latter study showed that when DTI was performed perpendicular to the transitional zone, type II collagen appeared sideways in the central portion of the articular cartilage.…”
Section: Discussionsupporting
confidence: 81%
“…On the other hand, the tract length and volume are strongly dependent on the number of directions, especially when they are lower than 40. 20 The number of directions might explain why the ICC was good‐to‐excellent for the DTI metrics (FA, MD, AD, and RD) and lower for tractography (tract number, volume, and tract length). It is noteworthy that with our technical settings, we still see visible tracts and measurable DTI metrics.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations